2015
DOI: 10.1007/978-3-642-25890-9_7
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Geochemistry of Tacaná Volcano-Hydrothermal System

Abstract: Tacaná hosts an active volcano-hydrothermal system, characterized by boiling temperature fumaroles, near the summit (3,600-3,800 m asl), and bubbling degassing thermal springs near its base (1,000-2,000 m asl). The magmatic signature of gases rising to the surface is attested by their high CO 2 contents (δ 13 C CO2 = −3.6 ± 1.3 ‰), and relatively high 3 He/ 4 He ratios (6.0 ± 0.9 R A ), with a CO 2 / 3 He ratio typical for the Central American Arc (2.3 × 10 10 -6.9 × 10 11 ). Such magmatic signature is practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This approach allows a detailed geochemical and isotopic characterisation of the gas sample, giving strong constraints on the subsurface temperature of the volcanichydrothermal systems and the gas source (Allard et al, 1991;Ohba et al, 2008;Rouwet et al, 2009;Vaselli et al, 2010). Nevertheless, given the high risk implied by direct sampling, routine sampling and analysis are hard to sustain in a continuous way (Symonds et al, 1994).…”
Section: Gas Measurements On Volcanoesmentioning
confidence: 98%
“…This approach allows a detailed geochemical and isotopic characterisation of the gas sample, giving strong constraints on the subsurface temperature of the volcanichydrothermal systems and the gas source (Allard et al, 1991;Ohba et al, 2008;Rouwet et al, 2009;Vaselli et al, 2010). Nevertheless, given the high risk implied by direct sampling, routine sampling and analysis are hard to sustain in a continuous way (Symonds et al, 1994).…”
Section: Gas Measurements On Volcanoesmentioning
confidence: 98%
“…EAR, Figure 11), and to mafic magmas. Stratovolcanoes or (dome) complex volcanoes with welldeveloped hydrothermal systems that provide the prototype settings to develop crater lakes on volcano summits (wet volcanoes; Caudron et al, 2015;Rouwet et al, 2015b), are relatively scarce in Africa. The EAR volcanism is MORB-or OIB-type leading to predominantly basaltic (Mt Cameroon; Mbassa et al, 2012;Kervyn et al, 2014;Adams et al, 2015;Nyamulagira, Nyiragongo;Pouclet et al, 2016;Karthala, outside the EAR;Class et al, 2009;Pelleter et al, 2014), or sporadically carbonatitic volcanism (Oldoinyo Lengai; Kervyn et al, 2014;Keller and Zaitsev, 2012;Weidendorfer et al, 2017).…”
Section: Conceptual Model: Why Are Maar Lakes So Dominant In Africa?mentioning
confidence: 99%
“…As many active volcanoes of CAVA, it hosts a volcanohydrothermal system which is displayed as numerous thermal manifestations including thermal springs at lower altitudes and steam vents close to the volcano summit. The geochemistry of thermal waters and steam vents have been studied by Rouwet (2006) and Rouwet et al (2009Rouwet et al ( , 2014. It has been shown that the thermal water of Tacana are CO 2 -enriched, of a rare SO 4 -HCO 3 composition (up to 1 g L −1 of each anion), and that the steam vents discharge vapor of CO 2 -H 2 S composition without "magmatic" HCl and SO 2 , with low H 2 and relatively low 3 He/ 4 He ratio of~5.5 Ra, where Ra is the 3 He/ 4 He air ratio (1.4 × 10 −6 ).…”
Section: Introductionmentioning
confidence: 99%